COUNTERING THE COUNTERPUBLIC? THE GERMAN #METOO NETWORK ON TWITTER - Martini, Franziska (AoIR Selected Papers of Internet Research, 2020)
Certain varieties of feminism have become more popular, and so have anti-feminist reactions to it with both sides competing for visibility. However, the (gendered) interplay between feminist and anti-feminist counterpublics is still uncharted. At the same time, research in the field of feminist media studies is beginning to address questions of power inequalities within feminist publics on social media platforms. This study sheds light on the networked structure of the German-language #MeToo protest on Twitter in order to reveal who succeeded in becoming visible and influential in this digital protest and in order to show differences in networking practices among those involved. Analyzing the Twitter interaction network around #MeToo over a period of three month, we find that – as expected – this network consists of some highly connected hubs and a majority of nodes with only few connections. The most central nodes, only 1.1 percent of the Twitter users involved, account for 35 percent of interactions within the network. Applying qualitative and quantitative content analyses, this study shows that Twitter accounts of traditional news media play a central role in the #MeToo network from the very beginning, indicating that protest networks are less equal and horizontal than often assumed. At the same time, k-core decomposition reveals that most Twitter users in the network’s core published mostly racist and anti-feminist content, indicating that few but very loud and well-connected voices used the #MeToo protest to strategically mobilize against migration in Germany and Austria.